A performance ethics of the 'real' abortive body: The case of Aliza Shvarts and 'Untitled [Senior Thesis], 2008'. (4th March 2011) - Hagen, Lisa Hall
In 2008 Aliza Shvarts, a senior at Yale University, proposed and executed a thesis project for her undergraduate art major. She artificially inseminated herself repeatedly over the course of nine months, then self-induced a miscarriage on the 28th day of her cycle using herbal abortifacients. She planned to project video of her miscarriages (filmed alone in a bathtub) onto the sides of a large cube, with blood from the miscarriages suspended under its surface. When word spread on the nature of her project, Shvarts was faced with a powerful furore from Yale, the media and the national public. 'Untitled [Senior Thesis], 2008' was never shown in public. This article considers how realness and visibility can define a performance ethics of the abortive body. Performing an abortion narrative within the confines of traditional performance does not necessarily provoke any discussion of ethical performance. However, by bringing in her own body and the question of 'realness', Shvarts's piece entered that realm. She disrupted perceptions of ethics in performance by enacting a bodily speech that took for its language a process normatively defined within a cultural code of moral permissibility.